Proceedings of ‏The 8th International Conference on New Ideas in Management, Economics and Accounting 2021
DOI: 10.33422/8th.imeaconf.2021.03.63
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Effect of Internal Audit, IT Capability and CRO Role in the Enterprise Risk Management Implementation on Firm Performance Moderated by Listed Status among Indonesian State-Owned Enterprises

Abstract: Managing and mitigating risks have become more critical than ever for the management of enterprises nowadays. The management of the enterprises must have a helicopter view in perceiving, analyzing, and assessing risks as it must be regarded from the entire enterprise's perspective (Jie Liu, 2012) as the risk is undoubtedly an inherent part of the corporate strategy of doing business (Dickinson, 2001). Furthermore, currently managing risk is not just doing risk assessment including how to mitigate risk but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The findings indicated that IA core and legitimate roles contribute to improving ERM effectiveness. Setiawan et al (2021) highlighted the significance of the IA role in the implementation of ERM in Indonesian State-Owned companies. This involvement included continuous monitoring of the implementation process, evaluating the overall effectiveness, and providing advisory services with recommendations for enhancing RM processes.…”
Section: Internal Audit's Role In Enterprise Risk Managementmentioning
confidence: 99%
“…The findings indicated that IA core and legitimate roles contribute to improving ERM effectiveness. Setiawan et al (2021) highlighted the significance of the IA role in the implementation of ERM in Indonesian State-Owned companies. This involvement included continuous monitoring of the implementation process, evaluating the overall effectiveness, and providing advisory services with recommendations for enhancing RM processes.…”
Section: Internal Audit's Role In Enterprise Risk Managementmentioning
confidence: 99%